Therapeutic evaluation of efficacy of intralesional bleomycin in common warts including palmo-plantar and periungual warts: a prospective study - Kumar, Prabal; Mehta, Karaninder Singh; Mahajan, Vikram; Chauhan, Pushpinder Singh (International Journal of Research in Dermatology, 2019)
Background: Commonly used destructive treatment modalities for common warts though effective, are associated with pigmentary changes, scarring and recurrences. Treatment with immune modulators or immunotherapy has shown variable results. We evaluated efficacy and safety of intralesional bleomycin for treating common warts including palmoplantar and periungual warts. Methods: Two hundred patients with common, palmar, plantar and periungual warts (having 753 warts) were treated with two intralesional injections of bleomycin 1 mg/ml at two weekly intervals. They were followed up at 4weeks and 12 weeks for cure, adverse effects and partial clearance or recurrence. Results: Only 183 (M: F 95:88) patients having 703 warts completed the study. Overall, complete clearance in 669 (95.16%) warts in 156 (85.2%) patients and partial clearance in 24 (3.4%) warts in 21 (11.4%) patients were observed. Patients with complete/partial clearance were highly satisfied from the treatment. Recurrence was seen in 6 (3.27%) patients. Most patients had injection site pain for 2-3 days not warranting discontinuation of treatment. Other adverse effects included temporary hyperpigmentation in 46, altered skin texture in 12 and injection site infection in 6 patients, respectively. Conclusions: Intralesional bleomycin appears effective, safe, and acceptable treatment modality for common warts including palmoplantar and periungual warts. It carries the advantage of low dose, insignificant adverse effects and high patient satisfaction.